If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18x + -1y = 9 Solving 18x + -1y = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'y' to each side of the equation. 18x + -1y + y = 9 + y Combine like terms: -1y + y = 0 18x + 0 = 9 + y 18x = 9 + y Divide each side by '18'. x = 0.5 + 0.05555555556y Simplifying x = 0.5 + 0.05555555556y
| 1.4/2.8= | | 15u+27-3=0 | | 0.8x-11=0.3x+41 | | 15u+27=3 | | 2.8/1.4= | | .05x+.30(400)=.10(x+400) | | 5x=-3+y | | 450-22x=0 | | 11(t-3)+3t=7(2t+5)-8 | | -44=4.4j | | 16y=-89+5x | | 12+x=-10 | | z+32z=126 | | 2a^2-a-3=0 | | 2(v+7)-5v=23 | | 6+0.1x=0.15x+8 | | 6a^2-7a-3=0 | | 5(x-5)=4(8-x)+3+x | | x=21+4y | | -16+15n=-7(-6+8n)+3 | | 6x-7=-7 | | a^2+a+8=118 | | 14.1-.3x=1.3x-4.2 | | 8.5*0.5= | | 4x^2+3x-10= | | x^2+x+1=21 | | 3c-12=45 | | 20+10x=14x | | 17=x+5 | | x^2+6x+8=35x^2 | | 39=9x-3x | | (x+35)+(4x-37)+x=964 |